Mindfulness Training to Lower Anxiety in New College Students - Aulia Suhesty; Miranti Rasyid; Diah Rahayu; Nadia Annabila; Theresia Dwi Uli (Indonesian Journal Of Educational Research and Review, 2023)
Anxiety is normal for every human being so that it is expected that every individual has the ability of mindfulness to reduce the anxiety that will be faced. Importance of mindfulness to reduce anxiety in college students. This study aims to analyze the effectiveness of the influence of mindfulness to reduce anxiety in new students. The research design used was a pretest-posttest test control group design. The research subjects were 26 new college students who were divided into 2 groups, namely 13 students in the experimental group and 13 students in the control group. The results of the analysis used the Wilcoxson test which compared the work readiness scores in the experimental group between before and after the training. The result showed a value of Z = -3.185, p = 0.000 (p <0.05) meaning that there was a difference in anxiety scores before and after being given the mindfulness training treatment, so there was a decrease in the level of significant anxiety after being given mindfulness training treatment. The results of the analysis using the results of the Mann-Whitney U Test obtained statistical results (Z) = -3.619 with a significance value (2-tailed) = 0.000 (p <0.05), meaning that there was a difference in the level of anxiety between the experimental group that was given treatment in the form of mindfulness training and the control group that was not given treatment in the form of mindfulness training.